EMI Practices and Sustainable Development Goals of Education in Nepal: A Narrative Inquiry - Khatri, Bimal (The Journal of Aadikavi, 2024)
This study investigates the complex relationship between the push for English Medium Instruction (EMI) in Nepal and the country's commitment to Sustainable Development Goal 4, which aims for inclusive and equitable quality education. While Nepal's national framework champions local knowledge and lifelong learning, a powerful trend is emerging among educators, parents, and policymakers who see EMI as a universal solution for educational improvement. This research, using a narrative inquiry approach, explores this contradiction. It finds that the motivation for EMI is often rooted in the perception that English unlocks global opportunities and social mobility. However, this paper argues that mandating English as the primary language of instruction, rather than empowering all students, can actually marginalize those from non-elite backgrounds, potentially pushing them out of the education system altogether and undermining the very goals of inclusion and equity that SDG 4 promises.